Laju Pertumbuhan Dan Tingkat Kelangsungan Hidup Jenis Karang Acropora Sp Dengan Metode Penempelan Fragmen Yang Berbeda - Ary Yancer Jimi Erika; Ramses Ramses; Lani Puspita (Faculty of Mathtmatics and Natural Sciences, 2019)
This study aims to determine the growth rate and survival of Acropora sp corals by attaching plastic and cement clamp fragments. As many as 64 Aropora sp fragments as high as 9-9.5 cm to be tested on two methods of attaching fragments. Acropora sp coral growth rate uses a method of sticking plastic clamps higher than using the cement attachment method. The survival rate of coral acropora sp using the cement attachment method is better than the method of attaching plastic clamps, which is 100% for the method of attachment with cement and 78% for the method of attaching plastic clamps.